Hygroscopicity of baru (Dipteryx alata Vogel) fruit - Daniel E. C. de Oliveira; Osvaldo Resende; Lílian M. Costa; Weder N. Ferreira Júnior; Silva Igor O. F. (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT With the knowledge on the hygroscopic equilibrium of the baru (Dipteryx alata Vogel) fruit, the product can be adequately handled to maintain the moisture content at the levels recommended for safe storage. Thus, this paper aimed to determine the water desorption isotherms of baru fruits at temperatures of 20, 25, 30 and 35 °C, and water activity between 0.14 and 0.80, and obtain the values of isosteric heat of desorption as a function of the equilibrium moisture content of the product. The equilibrium moisture content was obtained using the static-gravimetric method. Modified Halsey was the best model recommended to represent the hygroscopicity of baru fruits. The recommended moisture contents for safe storage of baru fruits are not more than 19.9, 19.3, 18.6 and 18.0 (%, d.b.) for the respective temperatures of 20, 25, 30 and 35 °C. The integral isosteric heat of desorption increases as the water content decreases, leading to an increment in the energy required to remove water from the product.